Influence of solubilizer PEG-40 hydrogenated castor oil on carbopol gels’ structural-mechanical properties - Ye. V. Gladukh; І. М. Grubnik; Н. Р. Kukhtenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Rheological properties affect all stages of the drug development – from development to production, the characteristics of the final products and stability.